(untitled) (Texas Journal of Agriculture and Biological Sciences, 2025)
Irrigation networks play a crucial role in the sustainable development of Uzbekistan’s economy and society, particularly ensuring efficient use of water resources and stability in the agricultural sector. The country has approximately 3.2 million hectares of irrigated land, which highlights the growing importance of rational management and protection of water resources. In recent years, due to climate change, industrialization, population growth, and decreasing water sources, the efficiency and condition of irrigation networks have deteriorated, leading to a decline in the meliorative quality of irrigated lands. For instance, although more than 248 billion Uzbek soms were spent on modernizing irrigation systems in the Aral Sea region during 2013–2017, issues related to water supply and land reclamation remain unresolved [1]. Therefore, designating and managing irrigation networks as protected zones to prevent water loss, protect the environment, and preserve the fertility of agricultural lands is an urgent task.